Identification of Proteins of Altered Abundance in Oil Palm Infected with Ganoderma boninense - Al-Obaidi, J.R.; Mohd-Yusuf, Yusmin; Razali, N.; Jayapalan, J.J.; Chin-Chong, T.; Md-Noh, N.; Junit, Sarni Mat; Othman, Rofina Yasmin; Hashim, Onn Haji (MDPI, 2014)
Basal stem rot is a common disease that affects oil palm, causing loss of yield and finally killing the trees. The disease, caused by fungus Ganoderma boninense, devastates thousands of hectares of oil palm plantings in Southeast Asia every year. In the present study, root proteins of healthy oil palm seedlings, and those infected with G. boninense, were analyzed by 2-dimensional gel electrophoresis (2-DE). When the 2-DE profiles were analyzed for proteins, which exhibit consistent significant change of abundance upon infection with G. boninense, 21 passed our screening criteria. Subsequent analyses by mass spectrometry and database search identified caffeoyl-CoA O-methyltransferase, caffeic acid O-methyltransferase, enolase, fructokinase, cysteine synthase, malate dehydrogenase, and ATP synthase as among proteins of which abundances were markedly altered.